Issues & Observations Taking Your Leadership to the Next Level - Eblin, Scott (Center for Creative Leadership, 2006)
The transition from manager to executive-level leader can be tricky and treacherous. Research has found that about 40 percent of new executives leave their jobs within the first eighteen months. The organizational toll of such failure is high: a recent Harvard Business School study found that the cost of a failed executive hire or promotion can run above USD2.5 million.
Online resource; Title from title page (viewed January 1, 2006)